1987
DOI: 10.1111/j.1432-1033.1987.tb13351.x
|View full text |Cite
|
Sign up to set email alerts
|

A two‐dimensional 1H‐NMR study of the dam methylase site: comparison between the hemimethylated GATC sequence, its unmethylated analogue and a hemimethylated CATG sequence

Abstract: We report two-dimensional NOE (NOESY) spectra on the sequence d(GCGATCATGG) d(CCATGATCGC) which contains the unmethylated dam site. As expected the DNA adopts a B-form conformation but appears to be distorted at the TG step of the second strand. This distorsion, probably bending, is not seen on the opposite strand. When the first strand is methylated on adenine in the GATC or CATG sequence the NOESY spectra indicate little or no change in the conformation. However the single strand-duplex exchange is slowed do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…5A). These findings support previous findings of base pair lifetimes in GATC sites, even though the previously adopted methods differ from ours (15).…”
Section: Characteristic Structural Identities Of the Hemimethylated Gsupporting
confidence: 83%
See 1 more Smart Citation
“…5A). These findings support previous findings of base pair lifetimes in GATC sites, even though the previously adopted methods differ from ours (15).…”
Section: Characteristic Structural Identities Of the Hemimethylated Gsupporting
confidence: 83%
“…1A), and there is no significant conformational difference between methylated DNA and unmethylated DNA with the same nucleotide sequence. These studies, however, demonstrated that the adenine N 6 hemimethylated DNA has a lower melting temperature and distinct dynamic characteristics represented by slow duplexsingle strand exchange (13)(14)(15)(16). Here, we investigate the solution structure and dynamics of two dodecamer DNA duplexes that contain either a single hemimethylated or unmethylated GATC site.…”
mentioning
confidence: 99%
“…6mA within GATC sequences causes slight DNA unwinding of 0.5°/methyl group (Cheng et al 1985). Consistent with these observations, two-dimensional NMR studies suggest that, in almost all cases, 6mA has only minor effects on helix conformation, as it retains the canonical B-form (Fazakerley et al 1985; Quignard et al 1985; Fazakerley et al 1987). 6mA occurring directly after thymines, on the other hand, causes severe unwinding and bending of the DNA helix relative to the canonical B conformation (Fazakerley et al 1989).…”
Section: Biological Functions Of 6mamentioning
confidence: 52%
“…The effects of 6mA on the thermodynamic stability and folding of DNA appear to be sequence-specific (Fazakerley et al 1987). Indeed, when 6mA occurs directly after a T this can cause a highly altered structure that is overwound and bent (Fazakerley et al 1989).…”
Section: Biological Functions Of 6mamentioning
confidence: 99%
“…The other goal of this study was to determine whether or not one or the other strand was significantly influenced by these substitutions and thus a preference of one over the other strand could be detected. (46)(47)(48). Substitutions in the sequences studied gave irregular responses.…”
Section: Discussionmentioning
confidence: 95%